Hemodynamic assessment and acute pulmonary vasoreactivity testing in the evaluation of children with pulmonary vascular disease. Expert consensus statement on the diagnosis and treatment of paediatric pulmonary hypertension. The European Paediatric Pulmonary Vascular Disease Network, endorsed by ISHLT and DGPK. (6th April 2016) - Apitz, Christian; Hansmann, Georg; Schranz, Dietmar
Abstract : Invasive assessment of haemodynamics (ventricular, pulmonary) and testing of acute vasoreactivity in the catheterisation laboratory remain the gold standard for the diagnosis of pulmonary hypertension (PH) and pulmonary hypertensive vascular disease. However, these measurements and the interpretation thereof are challenging due to the heterogeneous aetiology of PH in childhood and potentially confounding factors in the catheterisation laboratory. Patients with pulmonary arterial hypertension (PAH) associated with congenital heart disease who have a cardiovascular shunt need to undergo a completely different catheterisation approach than those with idiopathic PAH lacking an anatomical cardiovascular defect. Diagnostic cardiac catheterisation of children with suspected PH usually includes right and left heart catheterisation, particularly for the initial assessment (ie, at the time of diagnosis), and should be performed in experienced centres only. Here, we present graded consensus recommendations for the invasive evaluation of children with PH including those with pulmonary hypertensive vascular disease and/or ventricular dysfunction. Based on the limited published studies and our own experience we suggest a structured catheterisation protocol and two separate definitions of positive acute vasoreactivity testing (AVT): (1) AVT to assess prognosis and indication for specific PH therapy, and (2) AVT to assess operability of PAH associated with congenital heart disease. The protocol and the latter definitions may help in the systematic assessment of these patients and the interpretation of the obtained data. Beyond an accurate diagnosis in the individual patient, such a structured approach may allow systematic decision making for the initiation of a specific treatment and may assist in estimating disease progression and individual prognosis.